Case for staged thyroidectomy. Issue 10 (6th August 2020) - Ronen, Ohad; Robbins, K. Thomas; Olsen, Kerry D.; Shaha, Ashok R.; Randolph, Gregory W.; Nixon, Iain J.; Zafereo, Mark E.; Hartl, Dana M.; Kowalski, Luiz P.; Rodrigo, Juan P.; Coca‐Pelaz, Andrés; Mäkitie, Antti A.; et al.
Abstract: Recent modifications in the management of well‐differentiated thyroid cancer have resulted in significant alterations in clinical approach. Utilizing a series of preoperative and postoperative risk factors involving both the patient and the disease pathology, we offer the term "staged thyroidectomy" to help organize these risk factors for patients and the endocrine team to optimize management. This approach is intended to incorporate our latest nuanced understanding of certain endocrine pathology and may serve to optimize patient outcomes.